1995
DOI: 10.1111/j.1365-2265.1995.tb02600.x
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of oral ethanol on the hypothalamic‐pituitary‐adrenal axis in normal human subjects

Abstract: Intoxicating levels of ethanol per se do not result in activation of the hypothalamic-pituitary-adrenal axis in humans. However, gastrointestinal side-effects induced by the ethanol do result in such activation, which appears to be mediated by AVP as the dominant ACTH secretagogue. One of the factors which influences the blood ethanol level at which GI side-effects occur appears to be background alcohol intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…Specifically, several types of social behaviors including partner preference have been correlated with microsatellite length. In addition to vasopressin’s involvement in social behaviors, the neuropeptide levels are also affected by ethanol drinking and thought to play a role in the development of tolerance (Linkola et al, 1978; Hoffman et al, 1990; Inder et al, 1995; Harding et al, 1996; Rivier and Lee, 1996; Madeira and Paula-Barbosa, 1999; Silva et al, 2002). In addition, while one laboratory reported no effects of avpr1a deletion on ethanol intake (Caldwell et al, 2006), a more recent study found increased ethanol intake in avpr1a knockout mice (Sanbe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, several types of social behaviors including partner preference have been correlated with microsatellite length. In addition to vasopressin’s involvement in social behaviors, the neuropeptide levels are also affected by ethanol drinking and thought to play a role in the development of tolerance (Linkola et al, 1978; Hoffman et al, 1990; Inder et al, 1995; Harding et al, 1996; Rivier and Lee, 1996; Madeira and Paula-Barbosa, 1999; Silva et al, 2002). In addition, while one laboratory reported no effects of avpr1a deletion on ethanol intake (Caldwell et al, 2006), a more recent study found increased ethanol intake in avpr1a knockout mice (Sanbe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hypothalamicpituitary-adrenal (HPA) system alterations have been shown in healthy controls after acute alcohol intake (Inder et al, 1995;Waltman et al, 1993). However, acute ingestion of ethanol seems to stimulate the HPA system only when adverse effects occur, presumably due to vasopressin, which is increasingly released during nausea and emesis (Inder et al, 1995). Compared to acute intoxication, withdrawal seems to be an even stronger stimulus for the HPA system (Adinoff et al, 1991;Heuser et al, 1988;Von Bardeleben et al, 1989).…”
mentioning
confidence: 98%
“…Acute and also chronic alcohol consumption are known to affect virtually all endocrine functions. In particular, hypothalamicpituitary-adrenal (HPA) system alterations have been shown in healthy controls after acute alcohol intake (Inder et al, 1995;Waltman et al, 1993). However, acute ingestion of ethanol seems to stimulate the HPA system only when adverse effects occur, presumably due to vasopressin, which is increasingly released during nausea and emesis (Inder et al, 1995).…”
mentioning
confidence: 99%
“…Extensive literature implicates oxytocin and AVP in regulation of PP (28,39,40), and although we found some effects of alcohol or sex on these neuropeptide levels in a few brain regions (Table S1), there were no significant interactions to indicate a role for either of these neuropeptides in the sex-specific effects of alcohol on behavior. Because the roles of oxytocin and vasopressin are so essential to pair bonding, and because the effects of alcohol on these neuropeptide systems have been described previously (41)(42)(43)(44)(45)(46)(47)(48)(49)(50), it would be worth pursuing further experiments testing whether these systems do play a role in the effect of alcohol on PP that is simply not detected in changes in cellular or fiber peptide levels at 24 h of cohabitation.…”
Section: Discussionmentioning
confidence: 99%